Pemanfaatan Pekarangan Rumah Sebagai Upaya Ketahanan Pangan Keluarga - Nurmalia, Ana; Yumiati, Yossie; Yulihartika, Rika Dwi; Sugianto, Dapid (Universitas Dehasen Bengkulu, 2023)
Air Putih Village is a village that has just expanded from its main village on September 15 2011. Therefore Air Putih Village is still in the process of learning to become a more advanced and superior village in various sectors. The agricultural sector is very important in supporting the local, national and international economy. Of course, the agricultural sector is also expected to be able to become a supporting sector for Air Putih Village to become a village that is more independent in the economy and food. The problem that is often faced is the increase in the price of basic commodities which continues to soar, this of course contributes to the economic difficulties of the people who live in poverty, while vegetable crops support basic commodities. In order to meet the needs and convenience of food for the people of Air Putih Village, the Dehasen University Faculty of Agriculture Community Service team and partners agreed to hold a socialization for the use of yards. The yard of the house can be used as a planting medium for various vegetables to support people's daily food needs. This makes it easier for people to meet their needs for minerals and vitamins. Besides that, it can help the community's economy by reducing expenses for vegetable needs. So counseling and training was carried out on the use of home yards by planting various vegetables. The benefits of using yard land economically are able to reduce family expenses and even if it is occupied can provide additional family income.